2023
DOI: 10.1186/s13068-023-02338-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic analyses revealed regulation mechanism of mixotrophic Cylindrotheca sp. glycerol utilization and biomass promotion

Abstract: Background Diatoms have been viewed as ideal cell factories for production of some high-value bioactive metabolites, such as fucoxanthin, but their applications are restrained by limited biomass yield. Mixotrophy, by using both CO2 and organic carbon source, is believed effective to crack the bottleneck of biomass accumulation and achieve a sustainable bioproduct supply. Results Glycerol, among tested carbon sources, was proved as the sole that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The result indicating that mixotrophic media had only a slight effect on photosynthesis is consistent with previous results obtained for the diatoms Phaeodactylum tricornutum and Cylindrotheca sp. (Villanova et al 2017 ; Wang et al 2023 ). Thus, the metabolite levels observed in the CBB cycle of the mixotrophic OPMS 30543X group may have been higher than those in the autotrophic group because of the added glycerol effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicating that mixotrophic media had only a slight effect on photosynthesis is consistent with previous results obtained for the diatoms Phaeodactylum tricornutum and Cylindrotheca sp. (Villanova et al 2017 ; Wang et al 2023 ). Thus, the metabolite levels observed in the CBB cycle of the mixotrophic OPMS 30543X group may have been higher than those in the autotrophic group because of the added glycerol effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on P. lutheri have shown that more biomass is produced by mixotrophs than by autotrophs when cultured at appropriate light intensities (Bashir et al 2019 ). Moreover, in fucoxanthin-producing microalgae, HL intensity increases biomass production under autotrophic conditions while reducing fucoxanthin content (Wang et al 2023 ). To achieve maximum biomass and fucoxanthin production under mixed nutrition conditions, we determined the appropriate light intensity for OPMS 30543X.…”
Section: Discussionmentioning
confidence: 99%